2019
DOI: 10.3904/kjim.2016.324
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of fecal calprotectin in assessing inflammatory bowel disease activity

Abstract: FC was strongly associated with disease activity indices, serologic markers, and endoscopic activity in patients with IBD. QPOCT can be used more conveniently than ELISA to assess FC in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 29 publications
0
31
0
1
Order By: Relevance
“…Many physicians treating IBD still adopt a clinically-based management[ 56 ], even if recent data suggest that many IBD patients in clinical remission still have subclinical mucosal inflammation[ 57 ]. FC is correlated with clinical activity evaluated either by Sutherland criteria[ 58 ] or Partial Mayo Score[ 59 ]. In a study by Xiang et al[ 58 ], FC concentrations were useful to discriminate patients with active UC, inactive UC and control, with a cut-off point of 50 μg/g showing 91.9% sensitivity and 79.4% specificity; in patients with UC, FC had a better correlation with clinical activity than CRP.…”
Section: Fc In Ibdmentioning
confidence: 99%
See 1 more Smart Citation
“…Many physicians treating IBD still adopt a clinically-based management[ 56 ], even if recent data suggest that many IBD patients in clinical remission still have subclinical mucosal inflammation[ 57 ]. FC is correlated with clinical activity evaluated either by Sutherland criteria[ 58 ] or Partial Mayo Score[ 59 ]. In a study by Xiang et al[ 58 ], FC concentrations were useful to discriminate patients with active UC, inactive UC and control, with a cut-off point of 50 μg/g showing 91.9% sensitivity and 79.4% specificity; in patients with UC, FC had a better correlation with clinical activity than CRP.…”
Section: Fc In Ibdmentioning
confidence: 99%
“…Schoepfer and colleagues[ 63 , 64 ] found that FC was the only marker able to discriminate among mild, moderate and severe disease. A recent Korean study[ 59 ] highlighted how not only the ELISA, but also the Quantitative POCT predicted endoscopic inflammation (Mayo endoscopic score ≥ 1) in UC at a cut-off value of 201.3 μg/g and 150.5 μg/g respectively. In CD, a significant correlation with endoscopic activity was found both in colonic[ 33 ] and in small bowel CD[ 36 ], as well as with capsule endoscopy[ 65 ].…”
Section: Fc In Ibdmentioning
confidence: 99%
“…Unlike the FC concentration, which showed a significant difference between the age groups, no sig-Most of the reported articles had been about IBD patients, infant diarrhea, and meta-analysis results of the IBD patient group[17] as well as review articles[18][19][20]. Studies on FC are Thus, we conducted this study on healthy male and female adults residing in Jeju, between the age of 30 and 90, to understand the normal range of FC concentration.Another notable finding in the present study's results is that FC showed a statistically significant difference between males and females.…”
mentioning
confidence: 99%
“…As a result, fecal calprotectin is an indicator of in ammation in the gastrointestinal tract [17,18]. Calprotectin lasts for a week in the stool which makes it a good marker for detecting in ammation in the gut [17,19]. However, other studies with different results have been reported.…”
Section: Resultsmentioning
confidence: 99%